Struggle against corruption in foreign countries: politological aspect - Melnikov, Аdam P. (Journal of the Belarusian State University. Law, 2021)
The article outlines the up-to-date experience of struggle against corruption in different countries. The issues under analysis are organisational mechanisms of struggle against corruption as well as the legal basis of this struggle in different societies. The attention is focused on the three major aspects of anti-corruption struggle such as accountability and transparency of public officials activities, their income declaration as well as official ethics regulation.
Keywords: corruption; organisational mechanism of struggle against corruption; income declaration; ethic code for public officials; punitive measure